Relación entre la creación de empresas y el gasto del sector producción en el departamento de Loreto 2015 – 2021 - Vasquez Romaina, Daniel (2025)
This research analyzes the relationship between business creation and spending in the production sector in the department of Loreto during the period 2015-2021. Using a quantitative and correlational approach, quarterly data was examined to assess how public spending on production impacts business activity. The main statistical model used was Spearman's correlation coefficient, which made it possible to identify the nature and strength of the relationship between the variables. The results indicate a significant positive correlation between production sector spending and business creation, although the relationship was not extremely strong, suggesting the influence of other limiting factors. Moderate growth was also observed in the rate of business creation and improvements in budget execution, although the latter showed a weak correlation, evidencing deficiencies in resource management. The findings underscore the importance of strengthening institutional capacity, ensuring continuity of public support, and designing targeted interventions to overcome specific barriers faced by entrepreneurs in Loreto. The recommendations and proposals raised seek to improve the impact of public spending on the productive sector, promoting more inclusive and sustainable economic development in the region.